NBS-LRR protein Pik-H4 Interacts with OsBIHD1 to Balance Rice Blast Resistance and Growth by coordinating Ethylene-Brassinosteroid pathway - Liu, Hao; Dong, Shuangyu; Gu, Fengwei; Liu, Wei; Yang, Guili; Huang, Ming; Xiao, Wuming; Liu, Yongzhu; Guo, Tao; Wang, Hui; Chen, Zhiqiang; Wang, Jiafeng (Frontiers in Plant Science, 2017)
The regulation of innate immunity and plant growth, along with the trade-off between them, affects the defense and recovery mechanisms of the plant after it is attacked by pathogens. Although it is known that hormonal crosstalk plays a major role in regulating interaction of plant growth and PAMP-triggered immunity (PTI), the relationship between plant growth and effector-triggered immunity (ETI) remains unclear. In a large-scale yeast two-hybrid screening for Pik-H4-interacting proteins, a homeodomain transcription factor OsBIHD1 was identified, which is previously known to function in biotic and abiotic stress responses. The knockout of OsBIHD1 in rice lines carrying Pik-H4 largely compromised the resistance of the rice lines to M. oryzae, the fungus that causes rice blast. While overexpression of OsBIHD1 resulted in enhanced expression of the pathogenesis-related (PR) and ethylene (ET) synthesis genes. Moreover, OsBIHD1 was also found to directly bind to the promoter region of ethylene-synthesis enzyme OsACO3. In addition, OsBIHD1 overexpression or deficiency provoked dwarfism and reduced brassinosteroid (BR) insensitivity through repressing the expression of several critical genes involved in BR biosynthesis and BR signaling. During M. oryzae infection, transcript levels of the crucial BR catabolic genes (CYP734A2, CYP734A4, CYP734A6) were significantly up-regulated in OsBIHD1-OX plants. Furthermore, OsBIHD1 was found to be capable of binding to the sequence-specific cis-elements on the promoters of CYP734A2 to suppress the plant growth under fungal invasion. Our results collectively suggest a model that OsBIHD1 is required for Pik-H4-mediated blast resistance through modulating the trade-off between resistance and growth by coordinating brassinosteroid-ethylene pathway.